Progesterone change in the late follicular phase affects pregnancy rates both agonist and antagonist protocols in normoresponders: a case-controlled study in ICSI cycles - Berfu Demir; Inci Kahyaoglu; Altay Guvenir; Neslihan Yerebasmaz; Sadiman Altinbas; Berna Dilbaz; Serdar Dilbaz; Leyla Mollamahmutoglu (Taylor & Francis Group, 2016)
Objective: The aim of the presented study is to investigate the impact of progesterone change in the late follicular phase on the pregnancy rates of both agonist and antagonist protocols in normoresponders. Study design: A total of 201 normoresponder patients, who underwent embryo transfer were consecutively selected. 118 patients were stimulated using a long luteal GnRH agonist protocol and 83 using a flexible antagonist protocol. The level of change in late follicular phase progesterone was calculated according to the progesterone levels on the hCG day and pre-hCG day (1 or 2 days prior to hCG day) measurement. Results: Clinical pregnancy rates were comparable between long luteal and antagonist group (35.6 and 41%, respectively). The incidence of progesterone elevation on the hCG day was 11% in long luteal and 18% in antagonist group (p = 0.16). In pregnant cycles, p levels both on the hCG day and pre-hCG day measurement were significantly higher in antagonist than agonist cycles (p = 0.029, p = 0.038, respectively). The change of p level was statistically significant in non-pregnant cycles both for the agonist (-0.17 ± 0.07; 95% CI: −0.29 to −0.37) and antagonist groups (−0.18 ± 0.07; 95%CI: −0.31 to −0.04). Conclusions: Late follicular phase progesterone levels were stable during the cycles of pregnant patients irrespective of the protocols and were shown to be higher in pregnant patients in antagonist cycles when compared to agonist cycles.